Feminist peace research an introduction - Féron, Elise; Väyrynen, Tarja (New York, NY Routledge, 2024)
This textbook provides a comprehensive overview of the field of gender, feminism and peace. It is based on the argument that feminist thinking is necessary to understand and analyse the core issues in peace and conflict studies, and is fundamental to thinking about solutions to global problems and to promoting peaceful conflict transformation. The book centres alternative and critical approaches missing in mainstream peace research and brings forward feminist perspectives on traditional peace research topics such as militarism, peacekeeping, arms trade, and the articulation of different forms of violence. It also advances critical and alternative issues and topics that traditional peace research has sidelined, including, for example: artificial intelligence, technologies and peace; trauma and memory; human-nonhuman species relations; art; popular culture; postcolonial and decolonial feminist perspectives; the queering of war and peace. In sum, this textbook contributes to the visibility of these feminist critical approaches to peace research and makes them accessible to scholars and students interested in the subject. This book will be of much interest to students of peace studies, feminist theory, gender studies and International Relations
Feminist peace research: an introduction -- Section 1 - bodies in war and peace -- Conflicts and wars as corporeal experiences -- Female combatants -- Wartime sexual violence -- The gendered dimensions of forced displacement -- Post-conflict reconciliation and memory work -- Embodied war trauma and postmemory -- Section 2 - war and peace: an intersectional approach -- Matrices of domination, intersectionality and violent conflicts -- Gendered images and roles during violent conflicts -- Masculinities, nationalism and militarism -- Feminist approaches to genocide -- Feminist analyses of war economies -- Youth, conflict and peace -- Section 3 - subalternity, abjection and silencing in war and peace -- Decolonialising peacebuilding -- Post-conflict silencing -- Artificial intelligence and military technologies -- Alternative ontologies and conflict transformation -- Non-human animals in military institutions -- Section 4 - enabling and disabling environments -- Continuums of violence -- Post-war violence and impunity -- Disasters, famines and epidemics -- Climate crisis and justice -- Environmental peacebuilding -- Section 5 - power, resistance and activism -- Power and resistance in peacebuilding -- Feminist and women's peace activism -- Everyday peace -- Peacebuilding and reconciliation through the arts -- Epilogue: feminist imaginings of peace.
Keywords: Women and peace; Feminism